Erosion of the rule of law: a study of Canada and Ukraine - Haug, Harrison (My University, 2022)
Social inequality is present in every society, and every country has to deal with it differently. Some countries deal with social issues better than others. This paper examines the strength of the rule of law in Canada and Ukraine and the different factors that can affect that strength. Mainly, the factors that the paper focuses on are corruption and discrimination. When looking at something like corruption, we will see that some countries deal with this better than others, while some might deal with discrimination better. The point is that while every country faces these issues, they are not equally affected. The goal is to examine the similarities and differences between Canada and Ukraine regarding these issues.
Keywords: rule of law; corruption; discrimination